Measuring gaze patterns during colonoscopy: a useful tool to evaluate colon inspection?. Issue 12 (December 2016) - Dik, Vincent K.; Hooge, Ignace T.C.; van Oijen, Martijn G.H.; Siersema, Peter D.
Abstract : Background and objective: Considerable variation in adenoma detection has been shown between endoscopists, which may be explained by differences in colon inspection. Eye-tracking technology is an objective tool that detects differences in viewing patterns. We investigated the feasibility of eye-tracking technology during real-time, self-performed colonoscopies. Methods: In this pilot study, 10 endoscopists performed two colonoscopies each. A mobile eye-tracking system to register the right eye position was used to determine the gaze across four areas of interest of the endoscopy monitor (upper, lower, left, and right quadrant). The measured gaze across the endoscopy monitor was correlated with the gaze across the endoscopically visualized colonic surface. Results: Gaze patterns were measured successfully in 18 of 20 procedures. Significant differences in the time spent per area of interest were observed between endoscopists. The measured total gaze time per area of interest correlated strongly with the time spent on the corresponding area of the colonic surface (Pearson correlation coefficients ranging between 0.91 and 0.97). Endoscopists with more years of colonoscopy experience showed significantly higher percentages of overlap between the measured gaze position in the different areas of interest and the actual inspected area of the colonic surface ( r =0.65, P =0.02). More experienced endoscopists had nonsignificantly longer mean gaze times per area of interest ( r =0.52, P =0.06). Conclusion: Eye-tracking technology to measure gaze patterns of endoscopists during real-time, self-performed colonoscopies is feasible and may be used to evaluate and compare viewing behavior across the colonic surface of experienced endoscopists. Abstract : Supplemental Digital Content is available in the text.